Safe, Sustainable, and Recyclable by Design (SSRbD): A Qualitative Integrated Approach Applied to Polymeric Materials Early in the Innovation Process - Soeteman-Hernández, Lya G.; Cabrera, Géraldine; Huegun, Arrate; Outón, Pablo R.; Artous, Sébastien; Desrousseaux, Stephanie; Staal, Yvonne; Cazzagon, Virginia; Delpivo, Camilla; Ganszky, Daniel; Clavaguera, Simon (Sustainability & Circularity NOW, 2025)
The safe and sustainable by design (SSbD) concept integrates functionality with safety and sustainability aspects at an early phase of the innovation and product development process. A qualitative integrated safe, sustainable, and recyclable by design (SSRbD) approach was developed in a series of cocreation workshops involving risk assessors, toxicologists, eco-design, and sustainable development experts. The SSRbD approach consists of (1) identification of functionality, criticality, toxicity, environmental, social, circularity/recyclability, and economic impacts in a life cycle thinking perspective; (2) development of SSRbD strategies; and (3) verification of SSRbD strategies. The first two steps were applied to three case studies (building sector: new recyclable-by-design bio-sourced polyurethane (PU) to replace PVC (polyvinyl chloride) as insulating material for window frames; transport sector: fire-resistant, intrinsically recyclable epoxy-vitrimer materials for sustainable composites to replace metal for train body; and packaging sector: recyclable MultiNanoLayered (MNL) films to replace multilayer films for packaging with drastically reduced concentrations of compatibilizers). Guidance for identifying polymer material-relevant information needs was developed. In terms of internal organization, an interdisciplinary group for case study assessment was developed. Each case study comes with specific challenges and needs, which is why a tailor-made approach is required for the application of SSRbD of polymeric materials and products.
Keywords: Innovation; Safety; Sustainability; Recyclability; Polymeric materials; Integrated approach; SSbD